KARAKTERISTIK KEWIRAUSAHAAN DAN LINGKUNGAN BISNIS SEBAGAI FAKTOR PENENTU PERTUMBUHAN USAHA (Studi IKM di Sentra Kerajinan Rotan Amuntai Kab. Hulu Sungai Utara, Provinsi Kalimantan Selatan) - Edwin CahyaNingrum Setyawati; Nugraha Susanta Hari; Ilham Ainuddin (Universitas Diponegoro, 2013)
The purpose of this research is to know the characteristic of enterpreneurial business owners, conditions of business environment and the role of the business environment in the development of industries of rattan furniture, rattan weaving and lampit in Amuntai HSU, South Kalimantan. Population in this research is all businesses in Rattan Crafts Center in Amuntai HSU South Kalimantan. Sample in this research is taken using purposive and snowbal sampling. Data collecting is done by interview, observation and documentation methods. The result showed that enterpreneurship characteristics owned by the business owners are attitude of product innovation and authenticity, the willingness to take risk in having product diversity, and strong leadership in having harmonious relations with employees. The business owners have not yet had an attitude toward duties and maximum profit results within the internal and external business environment. Furniture and webbing rattan producers should be able to build duty-oriented attitude and an attitude towards maximum profit. They need to also be a risk-taker and a leader in facing the challenges of business world within internal and external business environment.